2023
DOI: 10.1017/bap.2022.21
|View full text |Cite
|
Sign up to set email alerts
|

Can We Talk About Pay Discrimination/Equal Pay/Strategic Compensation Practices? An Exploratory Study on Framing Gender Pay Inequity

Abstract: Situated within the public will and political will framework, this paper explores frames to address the social issue of gender pay inequity. Specifically, the authors examine whether demographic characteristics affect perceived acceptability of different frames describing gender pay inequity and perceptions of this social issue. First, the authors identified 26 terms used to discuss gender pay inequity; this list was narrowed to 12, representing four categories. Next, the authors solicited sentiment reactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Analysing various previous studies revealed that almost all reasons for an unequal distribution of incomes for male and female employees are derived from discrimination basics (Raile et al, 2023). As highlighted above, employers consider women, even with the same skills and characteristics as men, less qualified for specific positions or deserve to be promoted by the career ladder (Raile et al, 2023). In this regard, female workers are viewed differently based on certain stereotypes, prejudices, and opinions.…”
Section: Gender Pay Discriminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysing various previous studies revealed that almost all reasons for an unequal distribution of incomes for male and female employees are derived from discrimination basics (Raile et al, 2023). As highlighted above, employers consider women, even with the same skills and characteristics as men, less qualified for specific positions or deserve to be promoted by the career ladder (Raile et al, 2023). In this regard, female workers are viewed differently based on certain stereotypes, prejudices, and opinions.…”
Section: Gender Pay Discriminationmentioning
confidence: 99%
“…In this regard, female workers are viewed differently based on certain stereotypes, prejudices, and opinions. It is possible to mention at least four types of gender pay discrimination, such as stereotyping, taste-based, statistical, and normative discrimination (Raile et al, 2023). See Figure 2 for types of gender pay discrimination.…”
Section: Gender Pay Discriminationmentioning
confidence: 99%